2014
DOI: 10.1080/15295192.2014.972756
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Profiles of Mother–Child Interactions and Relations to Emerging School Readiness in African American and Latin American Children

Abstract: SYNOPSIS Objective This article examines ethnic similarities and differences in profiles of mother–child interaction qualities for low-income African American and Latin American mothers and associations with preschoolers’ emerging school readiness. Design Videotaped mother–child interactions were collected at age 2.5 years from a sample of African American (n = 192) and Latin American (n = 210) families. Profiles of maternal behavior were identified in person-centered within-group analyses of five ratings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…Results indicated that more consistent parenting approaches and greater use of teaching/explaining (i.e., describing alternative ways of behaving to the child) uniquely predicted better school readiness. These findings are consistent with extensive research underscoring that pedagogy-oriented, child-oriented parenting and discipline are conducive to positive outcomes for children's overall adjustment (Newland, 2015), including school readiness (Dyer et al, 2014;Estrada, Arsenio, Hess, & Holloway, 1987). Given that early learning and literacy activities are commonly cited as direct predictors of children's school readiness (Aldoney et al, 2015;Chazan-Cohen et al, 2009), it was also unsurprising that the current study found greater engagement in these activities at 2-3 years to be predictive of stronger number competence and receptive vocabulary skills at 4-5 years.…”
Section: Other Disciplinary Strategies As Predictors Of School Readsupporting
confidence: 87%
See 2 more Smart Citations
“…Results indicated that more consistent parenting approaches and greater use of teaching/explaining (i.e., describing alternative ways of behaving to the child) uniquely predicted better school readiness. These findings are consistent with extensive research underscoring that pedagogy-oriented, child-oriented parenting and discipline are conducive to positive outcomes for children's overall adjustment (Newland, 2015), including school readiness (Dyer et al, 2014;Estrada, Arsenio, Hess, & Holloway, 1987). Given that early learning and literacy activities are commonly cited as direct predictors of children's school readiness (Aldoney et al, 2015;Chazan-Cohen et al, 2009), it was also unsurprising that the current study found greater engagement in these activities at 2-3 years to be predictive of stronger number competence and receptive vocabulary skills at 4-5 years.…”
Section: Other Disciplinary Strategies As Predictors Of School Readsupporting
confidence: 87%
“…In the current study, psychological aggression by caregivers (i.e., raising their voice, scolding, or yelling at the child for misbehaving) predicted weaker number competence in preschoolers. This finding aligns with robust research showing the negative impact of harsh parenting on child development overall (e.g., Alink et al, 2009;Mendez et al, 2016) and on early cognitive and preacademic skill development specifically (Berlin et al, 2009;Dyer et al, 2014;MacKenzie et al, 2012;Pettit et al, 1997). Greater use of nonphysical punishment (e.g., taking away privileges or putting the child in his or her room) also predicted weaker performance in preschoolers' number competence.…”
Section: Other Disciplinary Strategies As Predictors Of School Readsupporting
confidence: 84%
See 1 more Smart Citation
“…Children living in households experiencing adversity have parents who are frequently less responsive and more intrusive (Dyer, Owen, & Caughty, ; Fuller, Bein, Kim, & Rabe‐Hesketh, ; Hart & Risley, ). Teenage mothers, for example, are often less verbally responsive and more intrusive than older mothers (Keown et al., ; Rafferty, Griffin, & Lodise, ).…”
Section: Maternal Responsiveness and Child Languagementioning
confidence: 99%
“…In particular, younger infants may benefit from successful redirection in order to acquire early wordobject associations (Matatyaho and Gogate 2008). For example, a positive association has been found between directive parenting and child language in cohorts of African-American children (Shimpi et al 2012, Dyer et al 2014, whilst a negative association has been established between directives and language in cohorts that are predominantly European-American (e.g., Masur et al 2005) or Australian . Feasibly the direction or strength of associations between directives and child language outcomes may differ by cultural group.…”
Section: Developmental Cultural and Socioeconomic Considerationsmentioning
confidence: 99%